Fluoride content in green tea infusions (Camellia sinensis) - Reto, Marcia (2015)
The aim of this work was to study the influence of green tea consumption on fluoride ingestion. The extraction conditions of fluorides from green tea infusions were defined and nine brands of green tea available in Portugal were analyzed. The quantification of fluorides in the green tea was preceded by the implementation and validation of the potentiometric method (commercial fluoride selective electrode). The concentration of fluorides in the samples ranged from 0.8 to 2.0 mg L-1.